IDNStudy.com, kung saan ang iyong mga tanong ay natutugunan ng mga eksaktong sagot. Hanapin ang impormasyon na kailangan mo nang mabilis at madali sa pamamagitan ng aming komprehensibo at eksaktong platform ng tanong at sagot.
Answer and step-by-step explanation:
To create the sequence, let's find the common difference to find the missing term which is the second term.
Use the formula for an arithmetic sequence:
An = A1 + (n - 1)d
where
An is the nth term,
A1 is the first term,
n is the number of terms, and
d is the common difference.
Let's substitute the given values to the formula. Then simplify.
An = A3 = 1/2
A1 = 12
n = 3
1/2 = 12 + (3 - 1)d
1/2 = 12 + 2d
1/2 - 12 = 2d
-23/2 = 2d
-23/2 /2 = 2d/2
-23/4 = d
Thus, the common difference is -23/4.
Let's find the second term of the sequence by subtituting the formulas again. Then simplify.
A2 = 12 + (2 - 1)(-23/4)
A2 = 12 + (1)(-23/4)
A2 = 12 + (-23/4)
A2 = 25/4
Check if the given third term will be the same after you add the common difference to the second term.
A2 + d = A3
25/4 + (-23/4) = 1/2
1/2 = 1/2